Sensory evaluation of four red hybrid tilapia (Oreochromis Sp.) strains among fish consumers (Journal of Tropical Resources and Sustainable Science (JTRSS), 2024)
The viability of tilapia in the aquaculture industry is due to the market demands that consumers decide. Since every aquaculture species had distinct sensory attributes, a hedonic sensory evaluation was performed to assess the sensory characteristics of the flesh of four red hybrid tilapia strains: (i) ?O.niloticus x ?O.niloticus (A)(MF280061), ?O.mossambicus x ?O.mossambicus (B) (MF509596), ?O.niloticus x ?O.mossambicus (C)(MF509597) and ?O.mossambicus x ?O. niloticus (D)(MF509598). Hedonic and ranking tests were carried out by 120 participants who assessed each strain's 25 g steamed flesh. The sensory analysis was carried out by using five hedonic scales. They participated through a volunteer invitation. The surveyed population participated by 62.50% and 37.50% females and males, respectively. Participants were asked to complete the questionnaires, including demographic questions hedonic scores, and rank according to their preferences. Means of sensory attributes were analysed using the Kruskal-Wallis test at p0.05) exist between strains in the sensory attributes related to taste, odour, and juiciness. Strain D had the highest scores in all sensory attributes compared to other strains. However, only the texture (3.97±0.71) attribute was found to be significantly different (p0.05). Nevertheless, strain D (141.00) was ranked significantly higher compared to other strains. Thus, the participant's distinct, undistinguishable sensory attributes revealed that all strains could be commercialised as table fish.
Keywords: red hybrid tilapia; sensory; hedonic; variation; aquaculture